2017
DOI: 10.5468/ogs.2017.60.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum placental growth factor and pregnancy-associated plasma protein A measured in the first trimester as parameters of subsequent pre-eclampsia and small-for-gestational-age infants: A prospective observational study

Abstract: ObjectiveTo examine the first-trimester maternal serum placental growth factor (PlGF) and pregnancy-associated plasma protein A (PAPP-A) levels in pregnancies associated with pre-eclampsia (PE) or small-for-gestational-age (SGA) infants, and determine the predictive accuracy of PlGF and of PAPP-A for either PE or SGA infants.MethodsThis prospective, observational study included 175 pregnant women, and of these women, due to participant withdrawal or loss to follow-up, delivery data were collected from the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
4
23
1
1
Order By: Relevance
“…Early diagnosis would enable closer monitoring and treatment of this condition, and may open the window for earlier intervention that might help reduce the associated risks to the fetus and the mother. In addition to investigations studying circulating free proteins and microRNAs for their biomarker potential, plasma extracellular vesicles, including exosomes, have been extensively studied in many medical fields for their diagnostic potential [38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis would enable closer monitoring and treatment of this condition, and may open the window for earlier intervention that might help reduce the associated risks to the fetus and the mother. In addition to investigations studying circulating free proteins and microRNAs for their biomarker potential, plasma extracellular vesicles, including exosomes, have been extensively studied in many medical fields for their diagnostic potential [38][39][40][41][42][43][44][45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of lower MAP with SGA may be attributed to its positive correlation with BMI [25]. About mean UtA PI, maternal characteristics and biochemical markers, several studies have demonstrated differences on pregnancies with SGA neonates at 11-13 weeks [26][27][28]. However, it is well known that first trimester screening of SGA neonates performs poorer than the screening for Preeclampsia [29,30].…”
Section: Main Findingsmentioning
confidence: 99%
“…Currently many biomarkers for early detection and prognosis of preeclampsia are investigated. The most widely used markers in clinical practice are: placental growth factor (PLGF) (Tsiakkas et al, 2015;Sung et al, 2017) and serum pregnancy-associated plasma protein-A (PAPP-A) (Kalousová et al, 2014;Patil et al, 2014). Unfortunately, their sensitivity and specificity is low yet.…”
Section: Introductionmentioning
confidence: 99%